Analisis Kinerja berdasarkan Hubungan Kerja, Komunikasi dan Tingkat Kesejahteraan Pegawai PT Perta Arun Gas Lhokseumawe - Haryadi, Haryadi; Muttaqim, Hakim (Singkite Journal, 2023)
This study aims to conduct an empirical analysis of employee perfor mance based on work relations, communication and level of welfare at PT Perta Arun Gas Lhokseumawe (PAG). Using survey research, quantitative method approach with path analysis. With exogenous variables respectively Work Relations, Communication and Level of Employee Welfare. Based on data collected through a rating scale questionnaire by 135 employees, a descriptive conclusion was obtained, that (a) work relations within the company, not yet optimal - with an achievement level of 79.9% of ideal conditions. (b) Interpersonal communication both within the work team and with the leadership has also been going well reaching 81%, (c) While the work welfare factor is good from the aspect of job security, family and work facilities in general it is good. The level of employee welfare reaches 79.20% and (d) the level of performance that is considered good reaches 78.99%. Statistically with path analysis the results are obtained; (1) There is a direct and indirect working relationship effect on the perfor mance of employees of 35.69%, (2) there is a direct and indirect effect of communi cation on the performance of employees of 40.74%, (3) it is proven that there is a direct and indirect effect of the level of welfare on employee performance of 44.07%, and (4) work relations, communication and the level of welfare jointly affect the performance of employees of PT. PAG Lhokseumawe, amounting to 40.1%